A catalogue of Indian Arctiinae (Erebidae, Lepidoptera) - Singh, Navneet; Joshi, Rahul; Kirti, Jagbir Singh; Bisht, Santosh Singh; Param, Harsimranjeet Singh (Zootaxa, 2021)
We present a catalogue of 673 species and nine subspecies of Indian Arctiinae in 175 genera which represents 6.11% of the global Arctiinae. Out of 673 species, a monogeneric tribe Amerilini is represented by four species (0.59 % of Indian Arctiinae and 6.06 % of global Amerilini), Arctiini are known by 180 species in 38 genera (26.74 % of Indian Arctiinae and 2.73% of global Arctiini), Lithosiini comprise 419 species in 128 genera (62.25% of Indian Arctiinae and 13.30% of global Lithosiini), and Syntomini account for 70 species in eight genera (10.40 % of Indian Arctiinae and 5.83% of global Syntomini). Information related to type localities, records from India with respective literature references, and the genus/ species synonyms is provided. Brief summaries for the four tribes of Indian Arctiinae, stating their Indian genus and species diversities, diagnostic characters of imagines are also provided. Furthermore, we present data on the distribution of the Arctiinae within the biogeographic zones of India. In addition, a brief analysis of the research history of Indian Arctiinae illustrates the general patterns of when and by whom the Indian species were described.